PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF FLAKES MADE FROM HEAT MOISTURE TREATMENT (HMT)-MODIFIED PURPLE SWEET POTATO AND MUNG BEAN - Ghina Qanitah Valerie; Shanti Fitriani; Emma Riftyan; Nizaha Juhaida Mohamad (Fakultas Pertanian Universitas Riau, 2026)
This study aimed to determine the optimal ratio of heat moisture treatment (HMT)–modified purple sweet potato flour and mung bean flour for flakes production. Flakes are instant foods typically made from cereal-based ingredients through baking. Purple sweet potato flour is a promising local raw material but has limited physical properties, which can be improved through HMT modification. Mung bean flour was added to enhance protein content. A completely randomized design with four treatments and four replications was applied. The treatments were ratios of HMT-modified purple sweet potato flour to mung bean flour: UK1 (80:20), UK2 (70:30), UK3 (60:40), and UK4 (50:50). Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results showed that the flour ratio significantly affected moisture, ash, protein, fat, and carbohydrate contents, as well as crispness retention and sensory attributes (color, aroma, taste, and texture). The best formulation was UK4 (50:50), with moisture content of 3.18%, ash 2.11%, protein 13.81%, fat 2.82%, carbohydrate 78.08%, and crispness retention of 8.33 minutes. Sensory evaluation indicated a brownish-purple color, slight mung bean aroma, characteristic mung bean taste, and crispy texture, with overall acceptance rated as “liked.”